The Cumacean Dimorphostylis elegans Gamô, 1960 (Crustacea), D. bathyelegans n. sp. and D. brevicarpus n. sp. from Japan - Akiyama, Tadashi (Zootaxa, 2011)
Dimorphostylis elegans Gamô, 1960 and two related new species, D. bathyelegans n. sp. and D. brevicarpus n. sp. are described. Dimorphostylis elegans were collected from the Pacific coasts of Honshu and Shikoku Islands, and the East China Sea, Japan, 74–443 m. As a result, D. latifrons Harada, 1960 from the Izu Peninsula, Japan is declared a junior synonym of D. elegans. Morphological variation of the carapace is discussed. Dimorphostylis bathyelegans, from southern coast of the Honshu Island and the East China Sea, is very similar to D. elegans, but is distinguished from the latter by the long telson and the third peduncle article of antenna 1 with more short setae. Depth of the habitat ranges from 495–918 m, which is the deepest known species in the genus. Dimorphostylis brevicarpus was collected from Kyushu and Nansei Islands, East China Sea, on sandy bottoms, 165–236 m deep. This species also resembles D. elegans, but is distinguished from the latter by (1) short carpus of pereopods 3–5, (2) anterior end of dorsolateral carina with 2 or 3 teeth, and (3) maxilliped 1 with a group of sharp spines on the ventral surface of basis, and (4) carapace covered with numerous small pits, with a tiny seta in each.